A holistic assessment framework for marine carbon dioxide removal options - Christian Baatz; Lukas Tank; Lena-Katharina Bednarz; Miranda Böttcher; Teresa Maria Morganti; Lieske Voget-Kleschin; Tony Cabus; Erik van Doorn; Tabea Dorndorf; Felix Havermann; Wanda Holzhüter; David Keller; et al. (Environmental Research Letters, 2025)
Marine carbon dioxide removal (mCDR) options could potentially play an important role in future CDR policy portfolios. They include, for example, ocean alkalinity enhancement, blue carbon projects such as mangrove cultivation, as well as sub-seabed storage of captured atmospheric CO 2 . In this paper we present a novel assessment framework designed for mCDR options. The framework provides important conceptual advancements to existing frameworks currently used to assess climate options: It clearly distinguishes between and allows for the assessment of both the feasibility and desirability of mCDR options, it makes explicit the evaluative standards upon which the assessment is based and it separates the descriptive listing of information from the evaluation of said information. The assessment framework aims to advance the debate on what role mCDR can and should play in responding to the climate crisis by providing a tool for both policymakers and stakeholders to assess mCDR options in a transparent and comprehensive way.
Keywords: 330; assessment framework; marine carbon dioxide removal; feasibility; desirability; climate change; assessment criteria; mitigation